(untitled) (Journal of the College of Basic Education, 2022)
That children represent the most important segment of society needs to be attention to preparing them to achieve sustainable development as well as the importance of childhood and the requirements of this phase of the possibilities to achieve the best result in the preparation of a positive generation and the Sui and the benefit to the community, especially our society and carries the tragedy as a result of the large number of violent practices and which affect negatively on the child’s thinking and generate a sense of persecution for that targeted current research: - Build Paranoid thinking the primary school pupils scale. Identify Paranoid thinking the primary school pupils. Know the differences in Paranoid thinking the primary school pupils according to the type variable (male – females). We define community Current search pupils primary school students in the province of Baghdad schools of the Directorate of Karkh third and aged (11-12) and both sexes and for the academic year (2015-2016) the number of the sample reached 300 pupils distributed according to variable sex and by 150 males and 150 females has researchers built Paranoid thinking by following scientific procedures measure also extracted to measure a number of characteristics and using t- test of one sample and t- test for two independent samples, the results showed:- The first goal has been achieved through the adoption of scientific procedures related to building Paranoid thinking in the third quarter scale The primary phase of the sixth grade have Paranoid thinking. There are differences between males and females in Paranoid thinking in favor of females. Based on the results the researchers have developed a number of recommendations and suggestions